Formal methods for industrial critical systems : 25th International Conference, FMICS 2020, Vienna, Austria, September 2-3, 2020, Proceedings /: 25th International Conference, FMICS 2020, Vienna, Austria, September 2-3, 2020, Proceedings. (2020) - Unknown
No abstract available